2015
DOI: 10.1155/2015/137246
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Violence: A Survey of Nationally Registered Emergency Medical Services Professionals

Abstract: Previous studies on violence against prehospital personnel have mainly reported on "verbal" and "physical" violence. This study explored how provider demographic and work-related characteristics were associated with five different forms of workplace violence (being cursed or threatened; being punched, slapped, or scratched; being spat upon; being stabbed/stabbing attempt; and being shot/shooting attempt). A cohort of nationally registered United States Emergency Medical Services professionals was surveyed to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…22,47 Gormley et al 44 found that personnel who had experienced violent patient encounters had more than double the median years of experience in a longitudinal cohort study of nationally registered EMTs. Likewise, Oliver and Levine 45 found that EMTs or their partners with more than ten years of work experience were more likely to experience violence in the form of being punched, slapped, or scratched compared to less experienced EMTs. These findings present inconclusive evidence supporting years of experience as a risk factor for EMS responders.…”
Section: Ems Responder-level Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…22,47 Gormley et al 44 found that personnel who had experienced violent patient encounters had more than double the median years of experience in a longitudinal cohort study of nationally registered EMTs. Likewise, Oliver and Levine 45 found that EMTs or their partners with more than ten years of work experience were more likely to experience violence in the form of being punched, slapped, or scratched compared to less experienced EMTs. These findings present inconclusive evidence supporting years of experience as a risk factor for EMS responders.…”
Section: Ems Responder-level Characteristicsmentioning
confidence: 99%
“…These four studies utilized survey data from nationally certified EMS responders participating in the Longitudinal EMT Attributes and Demographics Study (LEADS) administered by the National Registry of EMTs. 5,15,44,45 These data are the most comprehensive information on demographic characteristics and occupational injuries and exposures in EMS responders at the present time. Gormley et al 44 note that while the National EMS Certification is required in forty-six states, nationally certified EMS responders are found in each state.…”
Section: Estimates Of Violencementioning
confidence: 99%
See 2 more Smart Citations
“…Since the 1970s, violence against EMS responders has been recognized as an occupational hazard, and recent incidents indicate that the problem persists. In studies measuring career exposure to violence, between 57% and 93% of the EMS responders reported experiencing at least one act of verbal and/or physical violence (Bigham et al, 2014; Oliver & Levine, 2015). The extant literature describes verbal abuse, physical assault, and intimidation as the most frequently reported types of workplace violence in EMS (Bernaldo-de-Quiros et al, 2014; Boyle, Koritsas, Coles, & Stanley, 2007), with verbal violence described as the most prevalent form of violence (Gormley, Crowe, Bentley, & Levine, 2016; Rahmani, Hassankhani, Mills, & Dadashzadeh, 2012).…”
mentioning
confidence: 99%